ICT Competitiveness in Africa - Ewing, Javier; Chevrolier, Nicholas; Leenderste, Matthijs; Quigless, Maryanna; Verghese, Thomas (World Bank, Washington, DC, 2014)
The information and communication technology (ICT) sector has proven to be a strong driver of gross domestic product (GDP) growth in nations across the world. The ICT sector is socially and economically relevant to Africa in that it has been the major economic driver in Sub-Saharan Africa over the past decade. Although mobile and internet penetration remains comparatively low in Africa, never before in the history of the continent has the population been as connected as it is today. This summary outlines the current and historical landscape of the local ICT sector in Africa, explains the primary areas of ICT that will most benefit the continent, makes tactical recommendations to continue the momentum of growth, lists roadblocks to overcome in order to implement the recommendations, and describes case studies from specific African nations that currently lead the way.